Majalah Taman Nasjiah: Ruang Literasi Anak Indonesia Masa Pra-Kemerdekaan - Mutiara, Destitamutiara; Bariqi, Sirajuddin (Jurnal Studi Islam dan Kemuhammadiyahan (JASIKA), 2024)
'Aisyiyah's commitment to children's literacy has been carried out consistently since the women's organization found. Children's. One of the children's literacy roles carried out by 'Aisyiyah in the pre-independence era was by publishing children's magazines. The publication of Taman Nasjiah magazine has an important meaning for the development of women's and children's literacy, especially literacy that carries the breath of Islam. This research aims to reconstruct the lack of literature regarding the history of children's magazines while still carrying an Islamic breath. This research is a qualitative research with historical research methods by critically analyzing past records with research sources from Taman Nasjiah Magazine used four stages of heuristics, verification, interpretation and historiography. This research shows the results that Taman Nasjiah Magazine has the tagline "Madjalah anak-anak, terbit tiap-tiap boelan oleh Suara 'Aisjijah” which is intended for children aged 7-18 years, appeared in 1939 in collaboration with Suara 'Aisyiyah Magazine. The rubric provided by Taman Nasjiah is "Taman Pengetahoean". "Teka-teki", "Pekabaran", "Nasehat", "Tarich", "Leloetjon", "Cerita Anak" and tentative rubric